The Role of Parents in Helping Arabic Teachers to Improve Students’ Vocabulary - Mindy Gabriela; Garcia Cicerchi; Hernando Colin; Cara Ana (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
This article examines the role of parents in helping teachers in mastering Arabic vocabulary for elementery school students. In addition, this article aims to make parents aware of their role in helping the development of student's mastery of subject matter. This article aims to determine the contribution or role of parents in helping students master vocabulary. Focused first on mastery of vocabulary because vocabulary is a basic element in language. The research method used is a qualitative research method with a descriptive approach and survey study in accordance with the problem of how the role of parents in helping students master vocabulary at home. The results of this study indicate that parents have a significant role in mastering students' Arabic vocabulary through learning done from home. The increase in students' vocabulary mastery shows something more positive than before. In conclusion, parents have a big role in the learning process of students at home.